The Dark Side of Malleability: Incremental Theory Promotes Immoral Behaviors - Huang, Niwen; Zuo, Shijiang; Wang, Fang; Cai, Pan; Wang, Fengxiang (Frontiers in Psychology, 2017)
Implicit theories drastically affect an individual’s processing of social information, decision making, and action. The present research focuses on whether individuals who hold the implicit belief that people’s moral character is fixed (entity theorists) and individuals who hold the implicit belief that people’s moral character is malleable (incremental theorists) make different choices when facing a moral decision. Incremental theorists are less likely to make the fundamental attribution error (FAE), rarely make moral judgment based on traits and show more tolerance to immorality, relative to entity theorists, which might decrease the possibility of undermining the self-image when they engage in immoral behaviors, and thus we posit that incremental beliefs facilitate immorality. Four studies were conducted to explore the effect of these two types of implicit theories on immoral intention or practice. The association between implicit theories and immoral behavior was preliminarily examined from the observer perspective in Study 1, and the results showed that people tended to associate immoral behaviors (including everyday immoral intention and environmental destruction) with an incremental theorist rather than an entity theorist. Then, the relationship was further replicated from the actor perspective in Studies 2–4. In Study 2, implicit theories, which were measured, positively predicted the degree of discrimination against carriers of the hepatitis B virus (HBV). In Study 3, implicit theories were primed through reading articles, and the participants in the incremental condition showed more cheating than those in the entity condition. In Study 4, implicit theories were primed through a new manipulation, and the participants in the unstable condition (primed incremental theory) showed more discrimination than those in the other three conditions. Taken together, the results of our four studies were consistent with our hypotheses.